Engendered violence against women during partition in Bapsi Sidhwa's Cracking India and Amit Majmudar's partitions - Wei, Gabriel Clement Chua Chen (2016)
The 1947 Partition of British India marked the birth of two new nations and yet, at the same time, it was one of the largest human mass migrations in modern history (Butalia, 2000). While this historical turning point has given rise to the literary genre of Partition fiction, notable early works in English, such as Train to Pakistan (1956) by Khushwant Singh (1915-2014) and Sunlight on a Broken Column (1961) by Attia Hosain (1913-1998), focused mainly on macroscopic issues such as religious differences and socio-political unrest. This study, instead, aims to examine literary depictions of engendered violence against women set during the 1947 Partition of India, described by Butalia (100) as one of Partition’s “hidden” histories. It subsequently aims to discover the role of socio-cultural attitudes in stifling the voices of marginalised parties, notably those of women, in mainstream Partition narratives. In this study, engendered violence is described as a violation of women’s bodies, sexualities and psyches by men in general, carried out in various forms such as abduction, rape, honour killings, forced prostitution, forced marriages, forced religious conversions and bodily mutilations. That being said, this study shall focus solely on female characters depicted as victims of such violence in two selected texts of Partition fiction in English. The texts chosen for this topic are the novels Cracking India (1991) by Bapsi Sidhwa (b. 1938) and Partitions (2011) by Amit Majmudar (b. 1979). Both texts are examined based on a textual analysis method as the scope is narrowed down to scenes in the novels where various forms of engendered violence against women during Partition are depicted by the authors. By applying a “new Partition” approach initially identified by Rosemary Marangoly George(2007), this study utilises the works of “new Partition scholars”, namely Ritu Menon and Kamla Bhasin (1998) as well as Urvashi Butalia (2000) in delineating the concept of engendered violence against women during Partition as depicted in the selected texts. The study reveals that engendered violence against women during Partition, whether inflicted by men of the enemy or by men from within the community, has been depicted in various forms in the selected texts. In Cracking India, these include the abduction of Ayah, Hamida and the inmates of the Recovered Women’s Camp; the rape of Ayah and the Muslim women of Pir Pindo; the forced prostitution as well as the forced marriage and the forced religious conversion of Ayah, as well as the mutilated breasts of Muslim women on the train from Gurdaspur. On the other hand, in Partitions, these include the botched honour killing of Simran; the abduction of Simran and the human traffickers’ other female victims; the rape of Simran; the attempted forced prostitution of Simran and the human traffickers’ other female victims, as well as the mutilated Sikh women of Rawalpindi. All the aforementioned textual evidence reflects the common perception of the time, place and society that views women as symbolic constructions of male honour.